Kinerja Keuangan Dan Nilai Perusahaan: Bukti Empiris Dari Pengaruh ROA, ROE, NIM, dan DER (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of financial performance on firm value in the manufacturing sector listed on the Indonesia Stock Exchange. Financial performance in this study is measured through four main indicators: Return on Equity (ROE), Return on Assets (ROA), Net Interest Margin (NIM), and Debt to Equity Ratio (DER). Meanwhile, firm value is determined using market-based financial ratios. The research method used is a quantitative approach with multiple linear regression analysis. The research data were obtained from publicly available financial reports of manufacturing companies with a total of 84 observations during the study period. This research model was designed to test the extent of influence of each financial performance indicator on variations in firm value. The analysis results show that ROE, ROA, NIM, and DER simultaneously have a significant effect on firm value. Partially, ROE and NIM are proven to have a significant positive impact, meaning that the higher the two ratios, the higher the firm value. Conversely, ROA and DER show a significant negative effect, indicating that an increase in these two variables actually decreases the firm value. These findings indicate different dynamics between financial indicators in influencing market perception. The coefficient of determination (R²) of 30.6% confirms that the variation in firm value can be explained by the four independent variables in the model, while the remainder is influenced by other external factors not included in the study. Therefore, the results of this study provide important insights for management and investors regarding the role of financial indicators in shaping firm value. Management can use these findings to evaluate financial strategies, while investors can use this information to strengthen the basis for investment decisions.